The The Effect of Different Thermal Treatments on The Chemical Composition and Amino and Fatty Acids Profiles in Fish Artificial Diets - Al-Noor, Jalal M. (Mesopotamian Journal of Marine Sciences, 2024)
The study aimed to investigate the effects of different cooking methods (hot water T1, traditional stove T2 or autoclave cooking T3) on the chemical composition, fatty acid content and amino acid profile of fish diets. Variations in chemical composition moisture, ash, fat, and protein with fatty acid and amino acids profiles were also studied. The variations in chemical composition (moisture, ash, fat, and protein) (fatty acid amino acids) content and composition. The results showed variation in nutritional components with different cooking methods and significant differences (p < 0.05) between treatments. Diet-extracted oils contained 15 different fatty acids with varying percentages, with the total saturated fatty acids (SFA) being 23.72%, 23.97%, and 25.00% for diets T1, T2 and T3 respectively. The results indicated that the processed diets contained 18 amino acids, including both essential and non-essential amino acids, with a balanced composition and varying percentages among the processed diets. The total essential amino acids increased from 19.93 µg/100 µg protein in diet T3 to 20.36 µg/100 µg protein in diet T1 and 20.23 µg/100 µg protein in diet T2. The study concluded the importance of selecting the appropriate processing method for fish diet manufacturing and highlighted the need to examine changes in the chemical properties of nutritional components and the impact of temperature on nutrient digestibility and fish diet utilization., It seems that diet prepared using only hot water gave the best results.